The Sufficient and Necessary Condition of Lagrange Stability of Quasi-Periodic Pendulum Type Equations (Communications in Mathematical Research, 2021)
The quasi-periodic pendulum type equations are considered. A sufficientand necessary condition of Lagrange stability for this kind of equations is obtained.The result obtained answers a problem proposed by Moser under the quasi-periodiccase.
Keywords: Lagrange stability; pendulum type equation; KAM theorem.